Enzymatic Deinking of Xerographic Waste Paper with Non-ionic Surfactant - Chandranupap, Pravitra; Chandranupap, Panitnad (Applied Science and Engineering Progress, 2020)
Cellulase enzyme deinking of xerographic waste paper was investigated in this work. Enzyme action was assisted by using non-ionic surfactant (Triton X-100). Deinking steps were done as followed: converting xerographic waste paper to pulp, mixing pulp with enzyme and surfactant at 50°C for 30 min without pH adjustment, then removing ink from pulp slurry with flotation process. The results showed that cellulase deinking effectively removed ink from pulp slurry. That was indicated by the significantly decrease of ERIC (Effective Residual Ink Concentration) and pulp brightness improvement. Furthermore, the physical properties such as tensile index and tear index were improved with deinking that was influenced by enzyme dosage and surfactant addition.